Construction of toll canopy roof trusses steel structure - Akmal Hisham, Muhammad Aiman (Universiti Teknologi MARA, Perak, 2019)
This report briefly described and explains about the toll canopy roof trusses steel structure and how to construct it. The government of Malaysia has been spending around RM 5 billion on this SUKE project. The main objective of this highway was to reduce 35% traffic congestion from MRR2 to Kuala Lumpur. The steel structure has many advantages over the concrete structure and in this project, it can be seen how this steel structure can extend the distance from column to another in a relatively long path which is 74.6m roof structure which cannot be achieved using concrete structures. The objectives of this report are to determine the construction method of toll canopy roof trusses steel structure, to determine the test to be done and the problems that occurred and how to solve it.